2004
DOI: 10.1159/000077372
|View full text |Cite
|
Sign up to set email alerts
|

Renal Disease as a Predictor of Increased Mortality among Patients with Rheumatoid Arthritis

Abstract: Aims and Methods: Mortality among RA patients and controls was analyzed with special attention to renal disease in population-based material (originally screened in 1988) of 604 patients with RA (470 females, 134 males) and 457 age- and sex-matched controls (352 females, 105 males). In the original RA population, isolated hematuria (HU) was observed in 54, isolated proteinuria (PU) in 27, combined hematuria and proteinuria (HUPU) in 7, chronic renal failure (CRFtot) in 36 and isolated chronic renal failure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 19 publications
5
37
0
7
Order By: Relevance
“…Amyloidosis caused death in 8% of RA patients, thereby accounting for roughly one third of all deaths [6]. This is well within the range of 4-26% that other studies have reported as the prevalence rate of amyloidosis in RA patients [7].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Amyloidosis caused death in 8% of RA patients, thereby accounting for roughly one third of all deaths [6]. This is well within the range of 4-26% that other studies have reported as the prevalence rate of amyloidosis in RA patients [7].…”
supporting
confidence: 76%
“…In order to address this question, Sihvonen et al [6], in this issue of Nephron Clinical Practice, report on a prospective case-control study of Finnish RA patients with renal disease followed for 10 years. They found a significantly increased mortality in all RA patients (26 compared to 16% in the control group), with a hazard ratio of 1.78, which is in line with most other studies on the topic.…”
mentioning
confidence: 99%
“…Renal amyloidosis is associated with increased mortality in hemodialysis patients (36,39) and in patients with rheumatoid arthritis (40). The …”
Section: Some Reports Have Claimed That Renal Failure or Renal Dysfunmentioning
confidence: 99%
“…Kidney disease appeared in patients with RA most often during the first 10-15 years of RA disease; however, a significant percentage of patients with RA without baseline nephropathy progressed to CKD over time [9].…”
Section: Discussionmentioning
confidence: 99%
“…RA associated renal amyloidosis determines a higher mortality rate relative to rest of population [5]. Generally, the occurrence of proteinuria or CKD in patients with RA, was reported to associate with an increased risk of death [6], being identified also as an independent risk factor for cardiovascular events in such category [7].…”
Section: Introductionmentioning
confidence: 99%